Invasion-inhibitory antibodies elicited by immunization with Plasmodium vivax apical membrane antigen-1 expressed in Pichia pastoris yeast. - Vicentin, E; Françoso, K; Rocha, M; Iourtov, D; Dos Santos, F; Kubrusly, F; Sakauchi, M; Raw, I; Nosten, F; Rénia, L; Rodrigues, M; Russell, B; et al. (2014)
In a recent vaccine trial performed with African children, immunization with a recombinant protein based on Plasmodium falciparum apical membrane antigen 1 (AMA-1) conferred a significant degree of strain-specific resistance against malaria. To contribute to the efforts of generating a vaccine against Plasmodium vivax malaria, we expressed the ectodomain of P. vivax AMA-1 (PvAMA-1) as a secreted soluble protein in the methylotrophic yeast Pichia pastoris. Recognized by a high percentage of sera from individuals infected by P. vivax, this recombinant protein was found to have maintained its antigenicity. The immunogenicity of this protein was evaluated in mice using immunization protocols that included homologous and heterologous prime-boost strategies with plasmid DNA and recombinant protein. We used the following formulations containing different adjuvants: aluminum salts (Alum), Bordetella pertussis monophosphoryl lipid A (MPLA), flagellin FliC from Salmonella enterica serovar Typhimurium, saponin Quil A, or incomplete Freund's adjuvant (IFA). The formulations containing the adjuvants Quil A or IFA elicited the highest IgG antibody titers. Significant antibody titers were also obtained using a formulation developed for human use containing MPLA or Alum plus MPLA. Recombinant PvAMA-1 produced under "conditions of good laboratory practice" provided a good yield, high purity, low endotoxin levels, and no microbial contaminants and reproduced the experimental immunizations. Most relevant for vaccine development was the fact that immunization with PvAMA-1 elicited invasion-inhibitory antibodies against different Asian isolates of P. vivax. Our results show that AMA-1 expressed in P. pastoris is a promising antigen for use in future preclinical and clinical studies.